Comments to Belcher et al. 2018's critique of Hansson and Polk 2018. Issue 2 (11th March 2019) - Hansson, Stina; Polk, Merritt
Abstract: Assessing the value of transdisciplinary research is a complex and multifaceted enterprise allowing room for many perspectives. The Belcher et al. (2018) critique of our paper (Hansson and Polk 2018 ) seems to be based on different perspectives and different readings of prior work. These differences for us explains the majority of the criticisms raised against our paper. After having critically reread all of the involved texts we conclude that the analysis, overall conclusions and content of our paper are solid. However, the response to our paper raised some very nuanced and important points regarding how we understand and reference each other's work. In this comment we will respond to and explain the most important issues raised in relation to the aim of our paper, the validity of our empirical results and our interpretation of the reference texts. We find that from different perspectives and with different aims and methods our work comes to very similar conclusions regarding the RCL framework and its usefulness in promoting the societal impact of research.